Study guides

☆☆

Q: What is the answer to x4 plus x3 minus 14x2 plus 4x plus 6 divided by x minus 3?

Write your answer...

Submit

Related questions

4x + 20

x - 2

x = 0,1

(3x2 - 5x - 1)

2x^3 - 3x^2 + 4x - 3

3x

(x^2 + 1)(x^2 - 4x + 13)

minus 1

y = (4x+9)/(2x+3)2xy+3y = 4x+93y-9 = 4x-2xy3y-9 = x(2-2y)x = (3y-9)/(2-2y)So, inverse function is 3x minus 9 divided by 2 minus 27.

This would simplify as 4x-5

7x2 -4x -5x2 +2x = 2x2 -2x

(2x-1)(2x-1) = 4x^2 -4x + 1

6x - 4y

It is possible.

(4x - 1)(x - 5)

x(4x-2)

(4x - 3)(x - 1)

8x + 5z - 4x + 3z + 6 = 8x - 4x + 5z + 3z - 6 = 4x + 8z - 6

Because (x plus 3x) is 4x, and (-5 + 11) is 6.

8y-7x

-1 + 4x + 6x - 20 =10x - 19

Dividend: x3+4x2-9x-36 Divisor: x+3 Quotient: x2+x-12

x3-x2+5x-1 with remainder 7, which the final answer would be written as:x3-x2+5x-1+[7/(4x+3)]

It is a quadratic expression

(11 plus or minus the square root of 129) divided by 4x = 5.589454172900137x = -0.0894541729001368